2011
DOI: 10.1177/0143624411418153
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of heat insulation efficiency of building outer skins used for green building

Abstract: In general, the poor thermal insulation of building materials usually causes elevated room temperature, which not only reduces the comfort of the environment but also adds extra loading to the air conditioner. The objective of this study is to investigate the heat insulation efficiencies of building outer skins used for green building. A total of 25 types of multi-layer cladding materials and 9 types of single-layer skin materials made in Taiwan along with 4 types of overseas multi-layer skin materials were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Hence, the phase change temperature for pure sodium acetate ranges from about 45 C to 50 C, higher than the indoor thermal comfort zone. According to equation (9), its phase change enthalpy (i.e. fusion heat) is assessed to be 292.7 kJ/kg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the phase change temperature for pure sodium acetate ranges from about 45 C to 50 C, higher than the indoor thermal comfort zone. According to equation (9), its phase change enthalpy (i.e. fusion heat) is assessed to be 292.7 kJ/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 8 built the heat transfer models for building envelopes and stated that high thermal mass of PCM was necessary to maintain a comfortable indoor environment. Hou et al 9 investigated the effect of thermal mass on thermal performance and obtained the decrement factor based on the indoor and outdoor temperature difference. Then Cunha et al 10 found that inserting thermal insulation materials of low-heat transfer coefficient into building external walls is an effective way to decrease user loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the construction of green buildings is not mandatory but a market behavior. Green buildings refer to the buildings that save resources as much as possible, protect environment, and reduce pollution, and coexist harmoniously with the nature throughout the lifecycle [10]. As shown in Figure 1, the number of green building projects in China increased yearly from 2011 to 2018.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, convection is the means that heat flowsor circulates through a medium, which could be a liquid or a gas. Radiant heat proceedsin a straight line in waveform and heats bodiesin its pathway [9].…”
Section: Envelope Insulationmentioning
confidence: 99%